Selected Problems of Network Cooperation as a Tool for Integrated Development: The Three Seas Initiative in the Context of the Region’s Geopolitics - Kwiatosz, Katarzyna (Roczniki Nauk Społecznych, 2024)
The aim of the considerations was to analyze selected problems of network cooperation as a tool for integrated development on the example of the Three Seas Initiative. The analysis was carried out based on theoretical considerations regarding, among others, cooperation, partnership, relationships, cooperation and integration. The topicality of the discussed issues results from the dynamically changing geopolitical situation in Central and Eastern Europe. The article cites the key reasons for establishing and developing the Three Seas Initiative as an area of socio-economic cooperation. This has direct significance in the context of the security of Central Europe, which largely depends on developing cooperation, especially in the field of energy, transport and digitalization. The Three Seas Initiative, despite its relatively short period of operation, has already gained its international subjectivity, although it is worth mentioning that the Three Seas Initiative is still defining its identity, which results from the geopolitical complexities of the region. As part of this initiative, the countries of Central and Eastern Europe try to represent their interests at the EU forum, acting as a regional forum.